Economic Contribution of KVK Activities in Ujjain District of Madhya Pradesh - Saxena, Arvind; Dixit, A.K.; Tomar, D.S.; Kaushik, S.K. (Indian Journal of Extension Education, 2011)
Agriculture is very important and contributing greatly to the national development Agricultural development is intimately related with the application of new science and new technology in The study was conducted of Ujjain district of Madhya Pradesh. The Krishi Vigyan Kendra, Ujjain was established in the year 2004-05.farming. The study reflects successful diffusion of knowledge and technique for better farm production introduced by KVK in all the three villages. The level of adoption is high. A number of reasons are responsible for it. In economic sense this experiment has led to high farm production resulting thereby improvement in annual income. This has encouraged saving and discouraged indebtedness.